APOPT1/COA8 assists COX assembly and is oppositely regulated by UPS and ROS. Issue 1 (14th December 2018) - Signes, Alba; Cerutti, Raffaele; Dickson, Anna S; Benincá, Cristiane; Hinchy, Elizabeth C; Ghezzi, Daniele; Carrozzo, Rosalba; Bertini, Enrico; Murphy, Michael P; Nathan, James A; Viscomi, Carlo; Fernandez‐Vizarra, Erika; et al.
Abstract: Loss‐of‐function mutations in APOPT1, a gene exclusively found in higher eukaryotes, cause a characteristic type of cavitating leukoencephalopathy associated with mitochondrial cytochrome c oxidase (COX) deficiency. Although the genetic association of APOPT1 pathogenic variants with isolated COX defects is now clear, the biochemical link between APOPT1 function and COX has remained elusive. We investigated the molecular role of APOPT1 using different approaches. First, we generated an Apopt1 knockout mouse model which shows impaired motor skills, e.g., decreased motor coordination and endurance, associated with reduced COX activity and levels in multiple tissues. In addition, by achieving stable expression of wild‐type APOPT1 in control and patient‐derived cultured cells we ruled out a role of this protein in apoptosis and established instead that this protein is necessary for proper COX assembly and function. On the other hand, APOPT1 steady‐state levels were shown to be controlled by the ubiquitination–proteasome system (UPS). Conversely, in conditions of increased oxidative stress, APOPT1 is stabilized, increasing its mature intramitochondrial form and thereby protecting COX from oxidatively induced degradation. Synopsis: APOPT1 loss‐of‐function causes a leukoencephalopathy associated with mitochondrial cytochrome c oxidase (COX) deficiency in patients. APOPT1 does not play a role in apoptosis, but contributes to the biogenesis of cytochrome c oxidase (COX), which is part of the mitochondrial respiratory chain. Isolated COX deficiency in multiple tissues was caused by ablation of Apopt1 in mice. Mature APOPT1 is localized in the inner compartment of mitochondria participating in the intermediate stages of COX assembly. APOPT1 precursor is degraded by the Ubiquitin‐Proteasome System in non‐stress conditions. Under oxidative stress, the amount of intra‐mitochondrial APOPT1 was found to increase and to protect assembly COX intermediates from oxidative‐induced degradation. A new term for APOPT1 is proposed: COA8, for COX assembly 8 th factor. Abstract : APOPT1 loss‐of‐function causes a leukoencephalopathy associated with mitochondrial cytochrome c oxidase (COX) deficiency in patients. APOPT1 does not play a role in apoptosis, but contributes to the biogenesis of COX, which is part of the mitochondrial respiratory chain.